The influence of lifestyle habits on levels of depression among rural middle school students in Northeastern China - Zhao, JunCheng; Wang, Xiaoyin; Xu, Shiliang; Yan, Wenjing; Wang, Jingzhe; Wang, Ende; Liu, Tao; Hao, Ming (Frontiers in Public Health, 2024)
Background: Depression rates among adolescents have risen dramatically over the past decade.Therefore, preventing depression among adolescents is particularly important. Differences in lifestyle habits may play a role in depression.Purpose: This study aimed to explore the influence of living habits on depression levels among rural middle school students in Northeast China and to provide a theoretical basis for developing interventions to reduce depression levels in middle school students.Methods: A total of 296 middle school students aged 13-15 years from Benxi City, Northeast China completed the anthropometric measurements, Physical Activity Scale-3 (PARS-3), and the Self-Rating Depression Scale (SDS). Their average screen time in the most recent week, parents' education level, and monthly family income were collected through a questionnaire.Results: Females had higher depression scores than males (41.0±6.9 vs 37.9±8.0). Physical activity (β=-0.38, t= -7.06, P<0.01), family income (β=-0.20, t= -4.07, P<0.01), screen time (β=0.16, t=3.34, P<0.01), age (β=0.15, t=3.16, P<0.01), sex (β=-0.13, t= -2.74, P<0.01), and sleep quality (β=-0.08, t= -1.87, P<0.01) are important factors related to depression levels.The preliminary analysis results showed that among middle school students in rural Northeast China, the depression level of females was significantly higher than that of males. Poor quality sleep, low levels of physical activity, low household income, and long screen time were positively associated with depression. Therefore, strengthening physical activity, improving sleep quality, and reducing screen time are of clinical relevance in preventing and reducing depression.